Tidal and Bathymetry Characteristics in Dumai River Estuary in Dumai City, Riau Province - Maulana, Fariz; Mubarak, Mubarak; Rifardi, Rifardi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
This research was carried out in July 2023 in Muara Sungai Dumai, Dumai City, Riau Province. This study aims to conduct depth mapping analysis using echosounders based on reference corrections to tides. Tidal analysis is performed to determine reference values such as MSL (Mean Sea level) and tidal characteristics. The methods used are survey methods and quantitative analysis. The results showed that the waters of the Dumai River Estuary were mixed tide prevailing semi-diurnal with a formzahl value of 0.29. There is tidal asymmetry with the time to the high tide faster than the time to low tide. The depth ranges from 0.28 to 7.34 m, increasing to 40 m in the Rapat Strait. The weak current and the difference in HHWL values of 3.55 m and MSL 0.14 m affect water level rise due to bathymetric changes at high tide